Correlation of Collagen Triple Helix Repeat Containing 1 Overexpression With Lymph Node and Peritoneal Metastasis in Epithelial Ovarian Cancer. Issue 1 (1st January 2016) - Yang, Chang; Liu, Tianbo; Xia, Bairong; Gu, Lina; Lou, Ge
Abstract : Objective: This study aimed to reveal whether collagen triple helix repeat containing 1 (CTHRC1) was a predictor of peritoneal and lymph node metastases in epithelial ovarian cancer, which had not been researched by others previously. Materials and Methods: Western blot analysis showed that dramatic overexpression of CTHRC1 could be seen in most metastatic tissues. Univariate and multivariate logistic regression analyses demonstrated that overexpression of CTHRC1 was linked with peritoneal dissemination and lymph node metastasis in epithelial ovarian cancer. Results: The negative and sensitivity-predictive values of CTHRC1 staining were excellent for both lymph node and peritoneal metastases. The odds ratio of high versus low staining for peritoneal dissemination was 2.250 (95% confidence interval, 1.126–4.496), and that for lymph node metastasis was 13.102 (95% confidence interval, 6.036–28.439). Conclusions: Collagen triple helix repeat containing 1 may potentially be used as a predictive marker of clinical progression in ovarian cancer either alone or in combination with other markers.